Age Differences and Changes in Resources Essential to Aging Well: A Comparison of Sexagenarians, Octogenarians, and Centenarians. (9th August 2011) - Randall, G. Kevin; Martin, Peter; Bishop, Alex J.; Poon, Leonard W.; Johnson, Mary Ann
Abstract : This study examined change over time in five resources assessed by the Duke OARS Multidisciplinary Functional Assessment Questionnaire: social, economic, mental, physical, and functional resources. Two hundred and one participants in the Georgia Centenarian Study provided data for this longitudinal study: 70 sexagenarians, 63 octogenarians, and 68 centenarians. Those in their 60s and 80s were followed up within 60 months; due to mortality attrition, centenarians were followed up within 20 months. Centenarians experienced the lowest levels of resources relative to those in their 80s and 60s. Over time they primarily experienced loss in activities of daily living, highlighting that the ability to maximize gains and mitigate losses over time for older adults is highly associated with various resources essential to well-being. Findings suggest that older adults'—especially the very old—resources should be concurrently assessed in a multidimensional analysis by researchers and practitioners who work with older adults in various settings.